Faktor Determinan yang Memengaruhi Minat Berwirausaha Mahasiswa - Muhammad Aras; Chalid Imran Musa; Muhammad Rakib (Universitas Negeri Makassar, 2020)
This study aims to determine the determinants that influence student interest in entrepreneurship. This research is survey research. The population in the study were students in 2014, 2015 and 2016, with a total number of 581 students, then simple random sampling was chosen as many as 216 psychology students who had taken entrepreneurship courses. Data collection techniques used personal attitude scale, subjective norm scale, perception control scale, and student entrepreneurship interest scale through a questionnaire. Data were analyzed by regression and correlation tests. The results showed that: (i) there was a significant influence on personal attitudes towards student interest in dominant entrepreneurship in the medium category, (ii) there was a significant influence of subjective norms on dominant student entrepreneurial interest in the very low category, (iii) there was a positive influence and significant perception of behavioral control on dominant student entrepreneurial interest in the strong category compared to personal attitudes and subjective norms, (iv) together there is a significant influence of personal attitude, subjective norms and perception of dominant behavioral control has a very strong level of relationship with student entrepreneurial interest.